Differentiation Moderation Effects: Experiential Marketing And Green Marketing On The Purchasing Intention Of Motorcycle Scooters - Simamora, Virgo; Saputra, Bayu Dwi (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
Due to their flexibility and capacity to maneuver through heavy traffic, motorcycles are a common mode of transportation in Jakarta. The purpose of this study to examine the moderating effect of product differentiation on the impact of experiential marketing and green marketing on motorcycle scooter purchasing interest in Jakarta. The sampling technique used purposive sampling method. The primary data was collected by questionnaires distributed to motorcycle users in Jakarta with a sample of 96 respondents. The results showed that experiential marketing had a positive and significant effect on purchasing intention. Green products had a positive and significant effect on purchase intention. Also, product differentiation had a positive and significant effect on purchase intention. According to this study, there is no moderating effect of product differentiation on the impact of experiential marketing and green marketing on motorcycle scooter purchasing intention in Jakarta.